Nesting behavior of Melipona scutellaris (Latreille, 1811) (Research, Society and Development, 2021)
Ambience is one of the relevant factors in the rational breeding of bees. The uruçu bee (Melipona scutellaris) is a species native to Brazil, known for its large production of honey in relation to other meliponines and easy handling. Swarming, however, can destabilize honey production. The objective of this research was to study the nesting behavior of the M. scutellaris bee in octagonal hives exposed to abiotic factors in the environment. The experiment was carried out in two municipalities (Lagoa Seca and Areia) located in the micro-region of the Paraíba swamp. Twenty octagonal beehives were used, with 8 holes each, representing the cardinal (N, S, L, O) and collateral (NE, SE, SO and NO) points. The influence of the nesting time, evolution of the closing of the holes, effect of the direction and speed of the wind, and influence of the temperature and relative humidity of the air in the opening and closing of the nesting holes were evaluated. It is concluded that 1. The activity of closing the holes of the octagonal hive with M. scutellaris happens more frequently in the afternoon (from 12 pm to 4 pm); 2. In Lagoa Seca-PB, the M. scutellaris bees have a preference for nesting in the NE collateral orientation, avoiding the O orientation; 3. In Areia-PB, the M. scutellaris bees prefer the cardinal orientation N as a nesting point and avoid the SE orientation; 4. The increase in temperature and relative humidity increases the opening of the orifices in octagonal hives occupied by M. scutellaris; and 5. The increase in wind incidence and speed reduces the possibility of opening holes in octagonal hives populated with M. scutellaris.